Ablation Resistance Property of TiC/ZrO2 Coating Deposited by Plasma-spraying. Issue 8 (August 2017) - Zhuang, Ma; Wenzhi, Li; Lihong, Gao; Bo, Wen
Abstract: In the high temperature ablation process, the TiC coating will be oxidized to TiO2 . The thickness of molten TiO2 increases when the temperature is higher than 2000 °C, which decreases the bonding strength of the coating. In the present study, the TiC/ZrO2 coatings with different contents of high melting phase ZrO2 were deposited by plasma spraying, in order to improve the anti-scouring property of TiC coatings. The phase structure, microstructure and composition of the coatings, before and after ablation, were characterized by XRD, SEM and EDS, respectively. The ablation resistant mechanism of the coatings with high melting phase ZrO2 was discussed. Results indicate that the TiC/ZrO2 coating shows good ability of ablation resistance, and its mass loss is only 1.5×10 −4 g-cm −2 -s −1 at 2000 °C. The ZrO2 layer formed during the ablation can restrain the further oxidation of inner TiC and reduce the shearing force of oxyacetylene flame, which improves the anti-scouring property of the coatings.